Association of A1166C polymorphism in AT1 receptor gene with baroreflex sensitivity - Jíra, Miroslav; Závodná, Eva; Honzíková, Nataša; Nováková, Zuzana; Vašků, Anna; Izakovičová Hollá, Lydie; Fišer, Bohumil (Physiological research, 2010)
The aim of this study was to evaluate the association of A1166C polymorphism in angiotensin II type 1 receptor (AT1R) gene with baroreflex sensitivity (BRS in ms/mm Hg; BRSf in mHz/mm Hg) in man. BRS and BRSf were determined by a spectral method in 135 subjects (19-26 years) at a frequency of 0.1 Hz. Genotypes were detected by means of polymerase chain reaction and restriction analysis using enzyme DdeI. We compared BRS and BRSf among genotypes of this polymorphism. The frequency of genotypes of AT1R A1166C polymorphism was: 45.9 % (AA, n=62), 45.9 % (AC, n=62), 8.2 % (CC, n=11). Differences in BRS (p<0.05) and BRSf (p<0.01) among genotypes of this single nucleotide polymorphism were found (Kruskal-Wallis: BRS - AA: 7.9±3.3, AC: 8.6±3.6, CC: 5.9±2.3 ms/mm Hg; BRSf - AA: 12.0±4.0, AC: 12.0±5.0, CC: 8.0±3.0 mHz/mm Hg). Compared to carriers of other genotypes (AA+AC) the homozygotes with the less frequent allele (CC) showed significantly lower BRSf (Mann-Whitney: BRSf - AA+AC: 12.0±4.0, CC: 8.0±3.0 mHz/mm Hg; p<0.01) and borderline lower BRS (BRS - AA+AC: 8.2±3.5, CC: 5.9±2.5 ms/mm Hg; p=0.07). We found a significant association of A1166C polymorphism in AT1 receptor gene with baroreflex sensitivity. Homozygosity for the less frequent allele was associated with decreased baroreflex sensitivity.
Keywords: genotyp; mladý dospělý; Receptor, Angiotensin, Type 1; Risk Factors; Financing, Organized; receptor angiotensinu typ 1; Heart Rate; baroreflex; Genotype; Humans; lidé; Homozygote; krevní tlak; Risk Assessment; měření krevního tlaku; srdeční frekvence; Czech Republic; financování organizované; Signal Processing, Computer-Assisted; Gene Frequency; frekvence genu; Polymorphism, Single Nucleotide; Female; Male; Adult; odds ratio; mužské pohlaví; Phenotype; počítačové zpracování signálu; jednonukleotidový polymorfismus; ženské pohlaví; hodnocení rizik; fenotyp; homozygot; Young Adult; dospělí; Baroreflex; Blood Pressure; Česká republika; Odds Ratio; rizikové faktory; Blood Pressure Determination